HUBUNGAN KEKUATAN OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SAMPING PADA OLAHRAGA PENCAK SILAT - Suripto; Achmad Maulana; Asmau (Universitas Pahlawan Tuanku Tambusai, 2022)
This study was conducted with the aim of knowing the relationship between leg muscle strength and side kick speed in pencak silat extracurricular participants at SMA Negeri 2 Loa Kulu 2020-2021. In this study, the sample was taken through a purposive sample or a sample of 30 students. To obtain data in this study, the authors used the correlation method with test and measurement techniques, the data collected was then analyzed statistically using product moment correlation. After calculating with this technique, the number of rxy is 0.688, then these results are compared with the interpretation table and it turns out that the r value is located or at the level of 0.600 to 0.799 including in the category of a strong relationship. The amount of the contribution of the variable leg muscle strength to the speed of the side kick and the results obtained is 47.33% the amount of the variable contribution of the leg muscle strength to the speed of the side kick. Keywords: Limb Muscle Strength, Side Kick Speed